Climate Shocks and Farmers’ Agricultural Productive Investment: Resisting Risk or Escaping Production? - Zhou, Ziming; Yu, Zhiming; Gao, Sihan (Frontiers in Ecology and Evolution, 2022)
Climate shocks can increase uncertainty in agricultural production. Using data from the China Family Panel Studies (CFPS), this study examines the impact of climate shocks on farmers' productive investment and its mechanism of village public productive investment. The study found the following: (1) The impact of climate shocks have a significant impact on farmers’ productive investment choices. Farmers who are greatly impacted by climate shocks have a significantly lower probability of increasing their total productive investment. (2) In terms of investment content, climate shocks will reduce farmers' investment in machinery (invest1) and investment in the cost of seeds, fertilizers and pesticides (invest3) and increase investment in agricultural productive services (invest2). (3) However, there is heterogeneity in the village climate characteristics and farmers' risk preferences in this result. (4) From the perspective of the transmission mechanism, village public production investment has a moderating effect between climate shocks and farmer agricultural production investment. For total investment and invest3, village public production investment will weaken the main effect of climate shock, significantly reduce the impact of climate shock, and alleviate the inhibitory effect of climate shocks on farmers' investment. Agricultural productive services (invest2) will strengthen the main effect of climate shocks and promote farmer households’ agricultural productive service investment. The paper finally concludes and discusses some policy implications.